2003
DOI: 10.1037/0894-4105.17.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral eye movements enhance the retrieval of episodic memories.

Abstract: Two experiments examining effects of eye movements on episodic memory retrieval are reported. Thirty seconds of horizontal saccadic eye movements (but not smooth pursuit or vertical eye movements) preceding testing resulted in selective enhancement of episodic memory retrieval for laboratory (Experiment 1) and everyday (Experiment 2) events. Eye movements had no effects on implicit memory. Eye movements were also associated with more conservative response biases relative to a no eye movement condition. Episodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
276
5
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(306 citation statements)
references
References 51 publications
(67 reference statements)
17
276
5
8
Order By: Relevance
“…Given evidence that baseline hemispheric interaction is less in SR than in nSR individuals (Cowell et al, 1993;Habib et al, 1991;Witelson, 1985), the present results are partially supportive of the theory that eye movements enhance retrieval by increasing hemispheric interaction (Christman et al, 2003), because that theory predicts that eye movements should benefit SR individuals more than nSR individuals. This prediction was borne out: SR subjects benefited from eye movements on several measures, whereas nSR subjects benefited on none.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Given evidence that baseline hemispheric interaction is less in SR than in nSR individuals (Cowell et al, 1993;Habib et al, 1991;Witelson, 1985), the present results are partially supportive of the theory that eye movements enhance retrieval by increasing hemispheric interaction (Christman et al, 2003), because that theory predicts that eye movements should benefit SR individuals more than nSR individuals. This prediction was borne out: SR subjects benefited from eye movements on several measures, whereas nSR subjects benefited on none.…”
Section: Discussionsupporting
confidence: 75%
“…If eye movements enhance retrieval by increasing hemispheric interaction (Christman et al, 2003), then the manipulation should differentially affect groups that differ in baseline interaction. A group with less interaction, like SR individuals, may benefit from eye movements more than a group with greater interaction, like nSR individuals, because members of the former group have a larger margin for increases in interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also shown that saccadic EMs have greater effects on memory processing over smooth pursuit EMs (Christman et al, 2003), but research is yet to examine to what extent different EM tasks create saccadic movements during EMDR. Future research should also examine how much these aspects of dual-attention tasks relate to EMDR treatment outcome.…”
Section: The Effects Of Eye Movements Vs No Eye Movements In Emdrmentioning
confidence: 99%
“…EMs generate an increase in the vividness of episodic memory retrieval and expansion of association networks (Christman, Garvey, Propper, & Phaneuf, 2003) following 30 seconds of horizontal saccadic eye movements (but not smooth pursuit or vertical eye movements). 2.…”
Section: Jim Knipe's Summary Of the Researchmentioning
confidence: 99%